KEAKSARAAN PADA ANAK USIA DINI: LITERACY IN EARLY CHILDHOOD - Najib, Shofiyatun; Agustina, Hilda Dwi; Munawaroh, Hidayatu (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2024)
Early childhood children are those under 6 years of age, including those still in the womb, who are in the process of physical, mental, personality and intellectual growth and development, whether served or not served in early childhood education institutions. One of the things that needs to be considered in early childhood is literacy. Literacy in early childhood is a child's ability to speak to understand the arrangement of letters or writing. This is an initial introduction to children in their environment where there is writing or an arrangement of letters and vowels that form words such as apple, table, chair and so on.